I wanna be your girl. 1 - Takase, Umi (Takase, Umi, I wanna be your girl., 2025)
Being in love with your childhood best friend can be complicated, especially when, right before high school, she transitions to living as a girl. Hime has secretly been in love with her childhood best friend Akira for as long as she can remember. She was the first person who knew that Akira identified as a girl, and she made it her mission to be her Akira's protector against the world. Hime is thrilled that Akira has finally decided to live as her true self now that they are starting high school. However, as Akira starts to attract all types of attention, Hime takes it upon herself to aggressively stick up for Akira whenever necessary. Not wanting her to be singled out or bullied, Hime decides that her only option is to put herself in Akira's shoes. Hime dresses like a boy in support of the friend she loves, too bad her plan only backfires on them both. --